Depression in Diabetes: A Cross Sectional Survey among Patients Attending Diabetes Clinics - Latif Najmi, Zahoor Ahmed Shah, Muhammad Sohaib Ejaz Khan, Hoore Jannat, Saleh Yousef Alhedyan, Imran Joher, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Diabetes is a chronic disease that affects millions of people. Depression is reported to be a common comorbidity in diabetic patients. Depression in diabetic patients is associated with worse glycemic control, and increased risk of diabetes complications, including cardiovascular disease, neuropathy, and retinopathy Study design: It is a cross-sectional study conducted at Department of Medicine, Amna Inayat Medical College, Lahore for the duration of six months from April 2022 to September 2022. Material and Methods: The study included 150 diabetic patients who visited department of endocrinology and metabolism Services Hospital Lahore. There were 70 males and 80 females included in the study. 66 patients were in the range of 20-40 years and 84 were older than 40 years. 95 of them were illiterate while 55 were educated. Results: Total numbers of patients enrolled in this study were 150; among them 69 were type 1 diabetics while 81 had type 2 diabetes. Among type 1 diabetes 29 (42%) out of 69 patients were diagnosed with signs of depression whereas among type 2 diabetes the 40 (49%) patients were diagnosed with signs of clinical depression. It was found that there were 81 patients (54%) who were not diagnosed with any signs of clinical depression. Whereas 38 patients were suffering from mild form of depression. Conclusion: It was found that 46% of the diabetic patients suffered from depression. There were 54% diabetic patients that had no clinical signs of depression. There is a need to assess the signs of depression among diabetes patients. It can be an obstacle for the proper treatment of patient as such patients show non-adherence to their diabetes treatment because of poor mental health state. Keywords: Diabetes mellitus, depression and the blood glucose level